Pronunciation in foreign language classrooms: Instructors' training, classroom practices, and beliefs. (November 2019) - Huensch, Amanda
The goal of this work was to explore the training, classroom practices, and beliefs related to pronunciation of instructors of languages other than English. While several investigations of this type have been conducted in English as a second/foreign language contexts, very little is known about the beliefs and practices of teachers of languages other than English. It is unknown whether recent shifts to focusing on intelligibility, as advocated by some pronunciation scholars, are borne out in foreign language classrooms. To fill this gap, instructors of Spanish ( n = 127), French ( n = 89), and German ( n = 80) teaching basic language courses (i.e. the first four semesters) at 28 large (e.g. more than 15, 000 students), public universities in the United States completed an online survey reporting on their training, classroom practices, and beliefs. Similar to ESL/EFL contexts, the results indicated that instructors believe it is important to incorporate pronunciation in class and that it is possible to improve pronunciation. However, the findings also indicated that instructors have goals which simultaneously prioritize intelligibility and accent reduction. Implications include the need for research on which pronunciation features influence intelligibility in languages other than English and for materials designed to target these features.